Inorganic doped composite gel electrolyte, its preparation method and application
Patent Information
- Application Number
- CN202611325449.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]针对现有技术中存在的问题,本发明提供一种无机掺杂复合凝胶电解质及其制备方法和应用,从而解决传统锌空电池因采用液态电解质和刚性结构,在形变时易泄漏且存在安全隐患,而现有固态电解质又难以兼顾高离子电导率与优异的机械性能,无法满足柔性可穿戴设备需求的技术问题
本发明公开一种无机掺杂复合凝胶电解质的制备方法,该方法通过将聚乙烯醇(PVA)、壳聚糖(CS)与钠基蒙脱土(Na-MMT)复合,并利用聚乙二醇二缩水甘油醚(PEGDE)及丙烯酸原位聚合,形成了一个由共价键、氢键及物理缠结构成的多重交联三维网络骨架。这种致密且强韧的固态凝胶结构彻底替代了液态电解质,有效防止了电池在弯曲、拉伸等形变下的电解液泄漏,消除了安全隐患。其次,在提升性能方面,该方法利用先水后酸策略促使壳聚糖插层进入蒙脱土层间,不仅增强了机械强度,还通过层间阳离子交换增加了载流子密度;同时,PVA经冷冻-解冻循环形成的微晶物理交联点与均匀的孔道结构协同作用,为离子传输提供了高效通道。最后,凝胶网络中丰富的亲水基团(如-OH、-COOH)与多孔结构显著提升了电解质的吸液与保水能力,确保了在固态下仍具备优异的离子电导率。这种刚柔并济的微观结构设计,成功实现了高离子电导率与优异机械性能的协同统一,满足了柔性可穿戴设备对储能器件的严苛需求。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer and energy storage technology, and relates to an inorganic doped composite gel electrolyte, its preparation method and application. Background Technology
[0002] Against the backdrop of rapid global technological and industrial transformation, continuous population growth, and a significant increase in social production demands, resource consumption is accelerating, and a global energy crisis is gradually emerging. Simultaneously, the world is accelerating its energy structure transformation and carbon neutrality strategy. The traditional petrochemical energy system, due to its inherent defects such as high carbon emissions and high environmental impact, is no longer suitable for a green and low-carbon energy development pattern. In this context, society's demand for efficient and green energy storage technologies is becoming increasingly urgent, becoming a key driving force for energy transformation.
[0003] With the rise of sports and health monitoring devices, flexible wearable devices are developing rapidly, placing new demands on the form and performance of energy storage devices. Solid-state batteries, with their excellent flexibility, have thus become an indispensable core component. Compared to traditional rigid batteries, flexible batteries can adapt to complex deformations such as bending and stretching, meeting the diverse usage needs of wearable devices in various scenarios. Zinc-air batteries, due to their low-carbon and environmentally friendly production process and high theoretical energy density, are considered an ideal choice for wearable device energy storage systems, demonstrating broad application prospects.
[0004] However, traditional zinc-air batteries mostly employ liquid electrolytes and rigid structures, making them prone to electrolyte leakage during mechanical deformation, posing safety hazards and failing to meet the demands of flexible applications. Although solid-state electrolytes can effectively avoid leakage problems, current technologies still face challenges in balancing high ionic conductivity with excellent mechanical properties. Therefore, developing gel solid-state electrolytes that combine high conductivity, good water retention capacity, and robust mechanical properties has become crucial for achieving flexibility, safety, and long-cycle stability in zinc-air batteries. This technological breakthrough will provide important support for the multi-scenario application of flexible electronic devices and has significant research value and application significance. Summary of the Invention
[0005] To address the problems existing in the prior art, this invention provides an inorganic doped composite gel electrolyte, its preparation method, and its application, thereby solving the technical problems that traditional zinc-air batteries are prone to leakage and pose safety hazards when deformed due to the use of liquid electrolytes and rigid structures, while existing solid electrolytes are difficult to balance high ionic conductivity and excellent mechanical properties, thus failing to meet the requirements of flexible wearable devices.
[0006] This invention is achieved through the following technical solution: A method for preparing an inorganic doped composite gel electrolyte includes the following steps: S1: Add chitosan to sodium montmorillonite solution, adjust the pH to 3-6 to fully dissolve the chitosan, then add polyethylene glycol diglycidyl ether, stir evenly to obtain chitosan-sodium montmorillonite composite solution; S2: Polyvinyl alcohol is dissolved in deionized water, and after heating and stirring to dissolve, it is subjected to a freeze-thaw cycle to obtain a polyvinyl alcohol aqueous solution. The polyvinyl alcohol aqueous solution is mixed with a chitosan-sodium montmorillonite composite solution, and acrylic monomer, crosslinking agent and initiator are added. After stirring evenly, a heating polymerization reaction is carried out to form a composite gel. S3: The composite gel is immersed in an alkaline electrolyte for swelling treatment to obtain the inorganic doped composite gel electrolyte.
[0007] Preferably, the mass ratio of chitosan to sodium montmorillonite and polyethylene glycol diglycidyl ether is (0.1-1):(0.01-0.5):(0.1-1.5).
[0008] Preferably, the ratio of sodium-based montmorillonite to deionized water is (0.01-0.5) g:(10-30) mL.
[0009] Preferably, the mass ratio of polyvinyl alcohol to chitosan is (0.1-3):(0.1-1).
[0010] Preferably, in the polyvinyl alcohol aqueous solution, the ratio of polyvinyl alcohol to deionized water is (0.1-3) g:(1-50) mL.
[0011] Preferably, the ratio of the acrylic monomer to the crosslinking agent is (1-7) mL:(0.01-0.1) g.
[0012] Preferably, the alkaline electrolyte is a mixed solution of potassium hydroxide and zinc acetate.
[0013] Preferably, the swelling treatment time is 12-48 h.
[0014] An inorganic doped composite gel electrolyte is prepared by the method described above.
[0015] The above-mentioned inorganic doped composite gel electrolyte is used in flexible zinc-air batteries.
[0016] Compared with the prior art, the present invention has the following beneficial technical effects: This invention discloses a method for preparing an inorganic doped composite gel electrolyte. The method involves combining polyvinyl alcohol (PVA), chitosan (CS), and sodium montmorillonite (Na-MMT), and then using polyethylene glycol diglycidyl ether (PEGDE) and acrylic acid in situ polymerization to form a multi-layered cross-linked three-dimensional network framework composed of covalent bonds, hydrogen bonds, and physical entanglement. This dense and tough solid gel structure completely replaces the liquid electrolyte, effectively preventing electrolyte leakage under bending, stretching, and other deformations, thus eliminating safety hazards. Secondly, in terms of performance improvement, this method utilizes a water-first, acid-later strategy to encourage chitosan intercalation into the montmorillonite interlayer, enhancing mechanical strength and increasing carrier density through interlayer cation exchange. Simultaneously, the microcrystalline physical cross-linking points formed by the freeze-thaw cycle of PVA, along with the uniform pore structure, synergistically provide efficient channels for ion transport. Finally, the abundant hydrophilic groups (such as -OH and -COOH) and porous structure in the gel network significantly enhance the electrolyte's liquid absorption and water retention capabilities, ensuring excellent ionic conductivity even in the solid state. This flexible yet robust microstructure design successfully achieves a synergistic balance between high ionic conductivity and excellent mechanical properties, meeting the stringent requirements of flexible wearable devices for energy storage.
[0017] Furthermore, the mass ratio of chitosan to sodium montmorillonite and polyethylene glycol diglycidyl ether is (0.1-1):(0.01-0.5):(0.1-1.5), a specific ratio crucial for constructing a high-performance composite gel. Within this ratio range, chitosan and sodium montmorillonite form a uniform and stable intercalated composite structure, providing abundant ion transport sites for the gel. Simultaneously, an appropriate amount of PEGDE can undergo sufficient covalent cross-linking with the hydroxyl groups on the polymer chain, forming a robust three-dimensional network framework. This synergistic effect effectively balances the mechanical strength and flexibility of the gel, avoiding brittleness due to excessive cross-linking or loose structure due to insufficient cross-linking, thus ensuring that the electrolyte maintains high ion conductivity while possessing excellent mechanical properties.
[0018] Furthermore, the ratio of sodium-based montmorillonite to deionized water is (0.01-0.5) g:(10-30) mL. This range ensures that the sodium-based montmorillonite can be fully exfoliated and uniformly dispersed. Excessive concentration leads to montmorillonite agglomeration, preventing the formation of an effective intercalation structure and affecting the uniformity and performance of the final gel; insufficient concentration reduces reaction efficiency and makes it difficult to form a sufficient inorganic network framework. Within this optimized range, sodium-based montmorillonite can be uniformly dispersed in the form of nanosheets, laying a good structural foundation for subsequent composite with chitosan and the construction of interconnected ion transport channels, which is an important guarantee for achieving high gel performance.
[0019] Furthermore, the mass ratio of polyvinyl alcohol (PVA) to chitosan is (0.1-3):(0.1-1). PVA and CS are two core polymers constituting the organic network framework of the gel, and their ratio directly determines the overall performance of the gel. Within this ratio range, the flexibility and film-forming properties provided by PVA are optimally balanced with the abundant amino groups and biocompatibility provided by CS. By adjusting this ratio, the hydrophilicity, mechanical strength, and ionic conductivity of the gel can be precisely controlled. This ratio range provides a key control method for achieving the synergistic effect of high ionic conductivity and excellent mechanical properties of the gel electrolyte.
[0020] Furthermore, in the polyvinyl alcohol aqueous solution, the ratio of polyvinyl alcohol to deionized water is (0.1-3) g:(1-50) mL. This concentration range is crucial for the viscosity, film-forming properties, and subsequent freeze-thaw cycle performance of the PVA solution. Within this range, the PVA molecular chains can fully extend and form a homogeneous solution, providing a foundation for subsequent mixing with other components and the formation of a uniform gel network. Excessive concentration leads to excessively high solution viscosity, making uniform mixing difficult; excessively low concentration results in a sparse gel network with insufficient mechanical strength. Therefore, this ratio ensures that PVA can form an ideal physical cross-linked network, a prerequisite for obtaining a structurally uniform and stable composite gel.
[0021] Furthermore, the ratio of acrylic monomer to crosslinking agent is (1-7) mL:(0.01-0.1) g, which directly determines the crosslinking density of the polyacrylic acid (PAA) network formed by in-situ polymerization. Within this optimized range, the acrylic monomer can fully polymerize and form a dense and uniform covalent network with the crosslinking agent. A suitable crosslinking density not only firmly "locks" together components such as PVA, CS, and montmorillonite, significantly enhancing the mechanical strength and structural stability of the gel, but also forms a uniformly sized microporous structure, which is beneficial for electrolyte wetting and rapid ion migration, thereby synergistically improving the mechanical and electrochemical properties of the gel.
[0022] Furthermore, the alkaline electrolyte is a mixed solution of potassium hydroxide and zinc acetate, a choice optimized for the zinc-air battery system. KOH, as a strong base, provides a high concentration of OH-. - The presence of ions ensures the electrolyte has extremely high ionic conductivity, which is fundamental to achieving high power output in batteries. The introduction of zinc acetate, on the other hand, provides Zn within the gel network. 2+ Ions help form a stable electric double layer at the electrode / electrolyte interface and can effectively suppress dendrite growth and corrosion of the zinc anode during charge and discharge, thereby significantly improving the cycle stability and service life of zinc-air batteries.
[0023] Furthermore, the swelling treatment time is 12-48 hours, which is a key process parameter to ensure the gel electrolyte achieves optimal electrochemical performance. Within this time, the gel network can fully absorb the electrolyte and reach swelling equilibrium, allowing OH- to... - and Zn 2+ Plasma is uniformly distributed throughout the gel, forming highly efficient ion transport channels. If the swelling time is too short, the electrolyte absorption is insufficient, resulting in low ionic conductivity; if the time is too long, the gel network may over-swell, leading to decreased mechanical strength and even the dissolution of some components. Therefore, this time range ensures that the gel achieves high ionic conductivity while maintaining its structural integrity and excellent mechanical properties. Attached Figure Description
[0024] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0025] Figure 1 The following are bar charts showing the conductivity of the inorganic doped composite gel electrolytes prepared in Examples 1-5 of this invention. Figure 2 The images show the surface and cross-sectional scanning electron microscope (SEM) images of the inorganic doped composite gel electrolyte prepared in Example 4 of this invention, where (a) is a surface SEM image and (b) is a cross-sectional SEM image. Figure 3 The open-circuit voltage diagram (a) and power density diagram (b) of the flexible zinc-air battery assembled with the inorganic doped composite gel electrolyte prepared in Example 4 of the present invention are shown. Detailed Implementation
[0026] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0027] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0028] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0029] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0030] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0031] The purpose of this invention is to utilize the multiple hydrogen bond network formed between the hydroxyl groups of polyvinyl alcohol (PVA), the amino groups of chitosan (CS), and the silanol groups of sodium montmorillonite (Na-MMT), while simultaneously leveraging Na... MMT interlayer cation exchange increases carrier density, and combined with covalent and physical crosslinking to construct a stable multi-crosslinked framework, thereby synergistically improving the ionic conductivity, water retention capacity, and mechanical strength of the gel electrolyte. This provides an efficient and feasible material design and fabrication strategy for designing flexible zinc-air batteries with both high power density and long cycle stability, as well as wearable strain sensors.
[0032] Specifically, this invention provides a method for preparing an inorganic doped composite gel electrolyte, comprising the following steps: S1: Add chitosan to sodium montmorillonite solution, adjust the pH to 3-6 to fully dissolve the chitosan, then add polyethylene glycol diglycidyl ether, stir evenly to obtain chitosan-sodium montmorillonite composite solution; The mass ratio of chitosan to sodium montmorillonite and polyethylene glycol diglycidyl ether is (0.1-1):(0.01-0.5):(0.1-1.5). The sodium-based montmorillonite solution was prepared by adding sodium-based montmorillonite to deionized water and ultrasonically dispersing it for 10-60 min to obtain the sodium-based montmorillonite solution. The ratio of sodium-based montmorillonite to deionized water is (0.01-0.5) g: (10-30) mL; S2: Polyvinyl alcohol is dissolved in deionized water, and after heating and stirring to dissolve, it is subjected to a freeze-thaw cycle to obtain a polyvinyl alcohol aqueous solution. The polyvinyl alcohol aqueous solution is mixed with a chitosan-sodium montmorillonite composite solution, and acrylic monomer, crosslinking agent and initiator are added. After stirring evenly, a heating polymerization reaction is carried out to form a composite gel. In the polyvinyl alcohol aqueous solution, the ratio of polyvinyl alcohol to deionized water is (0.1-3) g:(1-50) mL; The mass ratio of polyvinyl alcohol to chitosan is (0.1-3):(0.1-1); The ratio of acrylic monomer to crosslinking agent is (1-7) mL:(0.01-0.1) g; S3: The composite gel is immersed in an alkaline electrolyte for swelling treatment to obtain the inorganic doped composite gel electrolyte.
[0033] The alkaline electrolyte is a mixed solution of potassium hydroxide and zinc acetate; The swelling treatment time is 12-48 h.
[0034] In this invention, polyvinyl alcohol can be replaced by any one or more of konjac glucomannan and alginate.
[0035] Sodium-based montmorillonite can be replaced by any one or more of nano-silica, kaolin, or attapulgite clay.
[0036] Chitosan can be replaced with any one or more of starch, cellulose, or hyaluronic acid.
[0037] The above process is as follows: a. Weigh 0.1-3 g of polyvinyl alcohol using an electronic balance, dissolve it in 1-50 mL of deionized water, place it in an oil bath at 50-100 ℃ and stir thoroughly until dissolved, then freeze-thaw at -20 ℃ 1-5 times, and record it as solution A.
[0038] b. Add 0.01-0.5 g of sodium montmorillonite to 10-30 mL of deionized water and sonicate for 10-60 min. This solution is called solution B.
[0039] c. Add 0.1-1 g of chitosan to B, adjust the pH to 3-6 by adding hydrochloric acid solution, and dissolve it evenly. Add 0.1-1.5 g of polyethylene glycol diglycidyl ether, stir thoroughly, and record this as solution C.
[0040] d. Mix solution A and solution B, stir for 0.5-1 h, and while stirring, add 1-7 mL of acrylic acid, stirring for another 0.5-1 h. Add 0.01-0.1 g of crosslinking agent N-N'-methylenebisacrylamide, stir for 0.5-1 h, then add 0.01-0.1 g of initiator ammonium persulfate, and continue stirring for 10-90 min. Place in an oven at 35-70℃ to polymerize for 1-3 h to form a gel.
[0041] e. Immerse the polymerized gel in a mixed solution of 6M potassium hydroxide and 0.2M zinc acetate for 12-48 h to swell, eventually forming an inorganic doped composite gel electrolyte.
[0042] This invention achieves uniform dispersion of sodium-based montmorillonite and formation of chitosan intercalation structures through a water-first, acid-later dispersion strategy. PVA, through freeze-thaw cycles, generates microcrystalline physical cross-linking points. Combined with PEGDE covalent cross-linking and PAA in-situ polymerization networks, a multi-cross-linking system synergistically involving hydrogen bonds, electrostatic interactions, and covalent bonds is constructed, forming a uniform and regular pore structure that promotes ion transport and endows the gel with high conductivity. This invention utilizes the polar hydrophilic groups such as -OH and -COOH in the gel electrolyte, along with the uniform pore structure, to synergistically enhance liquid absorption and water retention capabilities, thereby improving the battery's cycle life.
[0043] This invention uses sodium montmorillonite, polyvinyl alcohol, and chitosan as main raw materials. Based on a water-first, acid-later strategy, sodium montmorillonite and chitosan are mixed to form a chitosan-montmorillonite intercalated composite structure. Simultaneously, polyvinyl alcohol is pre-freezed and thawed at low temperatures to form a preliminary weakly cross-linked network. Polyethylene glycol diglycidyl ether undergoes ring-opening cross-linking with hydroxyl groups. Simultaneously, under the action of ammonium persulfate initiator, acrylic acid monomers undergo in-situ free radical polymerization, ultimately forming an inorganically doped composite gel electrolyte.
[0044] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0045] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0046] Example 1 A method for preparing an inorganic doped composite gel electrolyte includes the following steps: a. Weigh 0.1 g of polyvinyl alcohol using an electronic balance, dissolve it in 1.9 mL of deionized water, place it in an oil bath at 96 ℃ and stir thoroughly until dissolved, then freeze-thaw at -20 ℃ 5 times, and record this as solution A.
[0047] b. Add 0.15 g of sodium montmorillonite to 20 mL of deionized water and sonicate for 30 min. This solution is called solution B.
[0048] c. Add 0.5 g of chitosan to B, adjust the pH to 5 by adding hydrochloric acid solution, and dissolve it evenly. Add 0.8 g of polyethylene glycol diglycidyl ether and stir thoroughly. This solution is called C.
[0049] d. Mix solution A and solution B, stir for 0.5 h, then add 5 mL of acrylic acid while stirring, and stir for another 0.5 h. Add 0.02 g of crosslinking agent N-N'-methylenebisacrylamide, stir for 0.5 h, then add 0.05 g of initiator ammonium persulfate, and continue stirring for 30 min. Place in a 65℃ oven to polymerize for 1.5 h to form a gel.
[0050] e. Immerse the polymerized gel in a mixed solution of 6M potassium hydroxide and 0.2M zinc acetate for 48 h to swell, eventually forming an inorganic doped composite gel electrolyte.
[0051] Example 2 A method for preparing an inorganic doped composite gel electrolyte includes the following steps: a. Weigh 0.3 g of polyvinyl alcohol using an electronic balance, dissolve it in 5.7 mL of deionized water, place it in an oil bath at 96 ℃ and stir thoroughly until dissolved, then freeze-thaw at -20 ℃ 5 times, and record this as solution A.
[0052] b. Add 0.15 g of sodium montmorillonite to 20 mL of deionized water and sonicate for 30 min. This solution is called solution B.
[0053] c. Add 0.5 g of chitosan to B, adjust the pH to 5 by adding hydrochloric acid solution, and dissolve it evenly. Add 0.8 g of polyethylene glycol diglycidyl ether and stir thoroughly. This solution is called C.
[0054] d. Mix solution A and solution B, stir for 0.5 h, then add 5 mL of acrylic acid while stirring, and stir for another 0.5 h. Add 0.02 g of crosslinking agent N-N'-methylenebisacrylamide, stir for 0.5 h, then add 0.05 g of initiator ammonium persulfate, and continue stirring for 30 min. Place in a 65℃ oven to polymerize for 1.5 h to form a gel.
[0055] e. Immerse the polymerized gel in a mixed solution of 6M potassium hydroxide and 0.2M zinc acetate for 48 h to swell, eventually forming an inorganic doped composite gel electrolyte.
[0056] Example 3 A method for preparing an inorganic doped composite gel electrolyte includes the following steps: a. Weigh 0.5 g of polyvinyl alcohol using an electronic balance, dissolve it in 9.5 mL of deionized water, place it in an oil bath at 96 ℃ and stir thoroughly until dissolved, then freeze-thaw at -20 ℃ 5 times, and record this as solution A.
[0057] b. Add 0.15 g of sodium montmorillonite to 20 mL of deionized water and sonicate for 30 min. This solution is called solution B.
[0058] c. Add 0.5 g of chitosan to B, adjust the pH to 5 by adding hydrochloric acid solution, and dissolve it evenly. Add 0.8 g of polyethylene glycol diglycidyl ether and stir thoroughly. This solution is called C.
[0059] d. Mix solution A and solution B, stir for 0.5 h, then add 5 mL of acrylic acid while stirring, and stir for another 0.5 h. Add 0.02 g of crosslinking agent N-N'-methylenebisacrylamide, stir for 0.5 h, then add 0.05 g of initiator ammonium persulfate, and continue stirring for 30 min. Place in a 65℃ oven to polymerize for 1.5 h to form a gel.
[0060] e. Immerse the polymerized gel in a mixed solution of 6M potassium hydroxide and 0.2M zinc acetate for 48 h to swell, eventually forming an inorganic doped composite gel electrolyte.
[0061] Example 4 A method for preparing an inorganic doped composite gel electrolyte includes the following steps: a. Weigh 0.83 g of polyvinyl alcohol using an electronic balance, dissolve it in 16.6 mL of deionized water, place it in an oil bath at 96 ℃ and stir thoroughly to dissolve it, then freeze-thaw at -20 ℃ 5 times, and record it as solution A.
[0062] b. Add 0.15 g of sodium montmorillonite to 20 mL of deionized water and sonicate for 30 min. This solution is called solution B.
[0063] c. Add 0.5 g of chitosan to B, adjust the pH to 5 by adding hydrochloric acid solution, and dissolve it evenly. Add 0.8 g of polyethylene glycol diglycidyl ether and stir thoroughly. This solution is called C.
[0064] d. Mix solution A and solution B, stir for 0.5 h, then add 5 mL of acrylic acid while stirring, and stir for another 0.5 h. Add 0.02 g of crosslinking agent N-N'-methylenebisacrylamide, stir for 0.5 h, then add 0.05 g of initiator ammonium persulfate, and continue stirring for 30 min. Place in a 65℃ oven to polymerize for 1.5 h to form a gel.
[0065] e. Immerse the polymerized gel in a mixed solution of 6M potassium hydroxide and 0.2M zinc acetate for 48 h to swell, eventually forming an inorganic doped composite gel electrolyte.
[0066] Example 5 A method for preparing an inorganic doped composite gel electrolyte includes the following steps: a. Weigh 2.5 g of polyvinyl alcohol using an electronic balance, dissolve it in 47.5 mL of deionized water, place it in an oil bath at 96 ℃ and stir thoroughly to dissolve it, then freeze-thaw at -20 ℃ 5 times, and record it as solution A.
[0067] b. Add 0.15 g of sodium montmorillonite to 20 mL of deionized water and sonicate for 30 min. This solution is called solution B.
[0068] c. Add 0.5 g of chitosan to B, adjust the pH to 5 by adding hydrochloric acid solution, and dissolve it evenly. Add 0.8 g of polyethylene glycol diglycidyl ether and stir thoroughly. This solution is called C.
[0069] d. Mix solution A and solution B, stir for 0.5 h, then add 5 mL of acrylic acid while stirring, and stir for another 0.5 h. Add 0.02 g of crosslinking agent N-N'-methylenebisacrylamide, stir for 0.5 h, then add 0.05 g of initiator ammonium persulfate, and continue stirring for 30 min. Place in a 65℃ oven to polymerize for 1.5 h to form a gel.
[0070] e. Immerse the polymerized gel in a mixed solution of 6M potassium hydroxide and 0.2M zinc acetate for 48 h to swell, eventually forming an inorganic doped composite gel electrolyte.
[0071] Example 6 A method for preparing an inorganic doped composite gel electrolyte includes the following steps: a. Weigh 0.1 g of polyvinyl alcohol using an electronic balance, dissolve it in 1 mL of deionized water, place it in an oil bath at 50 ℃ and stir thoroughly until dissolved, then freeze-thaw at -20 ℃ 1-5 times, and record this as solution A.
[0072] b. Add 0.01 g of sodium montmorillonite to 10 mL of deionized water and sonicate for 10 min. This solution is called solution B.
[0073] c. Add 0.1 g of chitosan to B, adjust the pH to 3 by adding hydrochloric acid solution, and dissolve it evenly. Add 0.1 g of polyethylene glycol diglycidyl ether and stir thoroughly. This solution is called C.
[0074] d. Mix solution A and solution B, stir for 0.5 h, add 1 mL of acrylic acid while stirring, and stir for another 0.5 h. Add 0.01 g of crosslinking agent N-N'-methylenebisacrylamide, stir for 0.5 h, then add 0.01 g of initiator ammonium persulfate, and continue stirring for 10 min. Place in a 35℃ oven to polymerize for 1 h to form a gel.
[0075] e. Immerse the polymerized gel in a mixed solution of 6M potassium hydroxide and 0.2M zinc acetate for 12 h to swell, eventually forming an inorganic doped composite gel electrolyte.
[0076] Example 7 A method for preparing an inorganic doped composite gel electrolyte includes the following steps: a. Weigh 3 g of polyvinyl alcohol using an electronic balance, dissolve it in 50 mL of deionized water, place it in an oil bath at 100 ℃ and stir thoroughly until dissolved, then freeze-thaw at -20 ℃ 5 times, and record this as solution A.
[0077] b. Add 0.5 g of sodium montmorillonite to 30 mL of deionized water and sonicate for 60 min. This solution is called solution B.
[0078] c. Add 1 g of chitosan to B, adjust the pH to 6 by adding hydrochloric acid solution, and dissolve it evenly. Add 1.5 g of polyethylene glycol diglycidyl ether, stir thoroughly, and label this solution as C.
[0079] d. Mix solution A and solution B, stir for 1 h, add 7 mL of acrylic acid while stirring, and stir for another 1 h. Add 0.1 g of crosslinking agent N-N'-methylenebisacrylamide, stir for 1 h, then add 0.1 g of initiator ammonium persulfate, and continue stirring for 90 min. Place in a 70℃ oven to polymerize for 3 h to form a gel.
[0080] e. Immerse the polymerized gel in a mixed solution of 6M potassium hydroxide and 0.2M zinc acetate for 48 h to swell, eventually forming an inorganic doped composite gel electrolyte.
[0081] Example 8 A method for preparing an inorganic doped composite gel electrolyte includes the following steps: a. Weigh 2 g of polyvinyl alcohol using an electronic balance, dissolve it in 20 mL of deionized water, place it in an oil bath at 80 ℃ and stir thoroughly until dissolved, then freeze-thaw at -20 ℃ 3 times, and record this as solution A.
[0082] b. Add 0.3 g of sodium montmorillonite to 20 mL of deionized water and sonicate for 30 min. This solution is called solution B.
[0083] c. Add 0.5 g of chitosan to B, adjust the pH to 4 by adding hydrochloric acid solution, and dissolve it evenly. Add 0.8 g of polyethylene glycol diglycidyl ether and stir thoroughly. This solution is called C.
[0084] d. Mix solution A and solution B, stir for 1 h, add 5 mL of acrylic acid while stirring, and stir for another 1 h. Add 0.05 g of crosslinking agent N-N'-methylenebisacrylamide, stir for 1 h, then add 0.05 g of initiator ammonium persulfate, and continue stirring for 50 min. Place in a 50℃ oven to polymerize for 2 h to form a gel.
[0085] e. Immerse the polymerized gel in a mixed solution of 6M potassium hydroxide and 0.2M zinc acetate for 24 h to swell, eventually forming an inorganic doped composite gel electrolyte.
[0086] Figure 1 The figures show the conductivity histograms of the inorganic doped composite gel electrolytes prepared in Examples 1-5 of this invention. As can be seen from the figures, the conductivity of the electrolyte reaches its highest value, approximately 500 mS / cm, when the PVA:CS mass ratio is 5:3. -1 The conductivity was significantly better than other ratios; however, when the ratios were 1:5, 3:5, 5:5, and 5:1, the conductivity was lower than this peak value. Among them, the conductivity at the 3:5 and 5:5 ratios was similar, approximately 400 mS / cm. -1 At ratios of 1:5 and 5:1, the value is slightly higher, approximately 440-450 mS / cm. -1 This indicates that a PVA to CS ratio that is too high or too low is not conducive to ion conduction, while a 5:3 ratio is most conducive to the formation of efficient ion transport channels.
[0087] Figure 2 The images show the surface and cross-sectional scanning electron microscope (SEM) images of the inorganic doped composite gel electrolyte prepared in Example 4 of this invention, where (a) is a surface SEM image and (b) is a cross-sectional SEM image. From the surface morphology (a), it can be seen that the gel electrolyte exhibits a uniform and dense porous network structure with a relatively regular pore distribution. This structure is beneficial for electrolyte wetting and rapid ion transport. From the cross-sectional morphology (b), the material exhibits a distinct layered or oriented channel structure with good pore connectivity. This unique three-dimensional interconnected porous framework not only provides abundant ion transport pathways but also helps alleviate volume expansion during charging and discharging, thus confirming that the composite gel electrolyte has excellent microstructural characteristics, providing a structural basis for its good electrochemical performance.
[0088] Figure 3 The figures show the open-circuit voltage (a) and power density (b) of the flexible zinc-air battery assembled with the inorganic doped composite gel electrolyte obtained in Example 4 of this invention. As can be seen from the figures, in... Figure 3 In the open-circuit voltage test (a), the flexible zinc-air battery exhibited excellent open-circuit voltage stability, maintaining a voltage of around 1.36 V for 1000 seconds, slightly higher than the 1.33 V of pure PAA electrolyte, indicating that it has a lower risk of internal short circuit and better interface compatibility. Figure 3 The power density curve in (b) further confirms the superiority of the electrolyte, with the flexible zinc-air battery achieving a maximum power density of 179.4 mW / cm². -2 It is significantly better than the 125 mW cm⁻¹ of PAA electrolyte. -2 Furthermore, its discharge curve is flatter, showing lower internal resistance and higher energy output efficiency, which is mainly due to the excellent ionic conductivity and stable electrode / electrolyte interface of the composite gel electrolyte.
[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing an inorganic doped composite gel electrolyte, characterized in that, Includes the following steps: S1: Add chitosan to sodium montmorillonite solution, adjust the pH to 3-6 to fully dissolve the chitosan, then add polyethylene glycol diglycidyl ether, stir evenly to obtain chitosan-sodium montmorillonite composite solution; S2: Polyvinyl alcohol is dissolved in deionized water, and after heating and stirring to dissolve, it is subjected to a freeze-thaw cycle to obtain a polyvinyl alcohol aqueous solution. The polyvinyl alcohol aqueous solution is mixed with a chitosan-sodium montmorillonite composite solution, and acrylic monomer, crosslinking agent and initiator are added. After stirring evenly, a heating polymerization reaction is carried out to form a composite gel. S3: The composite gel is immersed in an alkaline electrolyte for swelling treatment to obtain the inorganic doped composite gel electrolyte.
2. The method for preparing an inorganic doped composite gel electrolyte according to claim 1, characterized in that, The mass ratio of chitosan to sodium montmorillonite and polyethylene glycol diglycidyl ether is (0.1-1):(0.01-0.5):(0.1-1.5).
3. The method for preparing an inorganic doped composite gel electrolyte according to claim 1, characterized in that, The ratio of sodium-based montmorillonite to deionized water is (0.01-0.5) g: (10-30) mL.
4. The method for preparing an inorganic doped composite gel electrolyte according to claim 1, characterized in that, The mass ratio of polyvinyl alcohol to chitosan is (0.1-3):(0.1-1).
5. The method for preparing an inorganic doped composite gel electrolyte according to claim 1, characterized in that, In the polyvinyl alcohol aqueous solution, the ratio of polyvinyl alcohol to deionized water is (0.1-3) g:(1-50) mL.
6. The method for preparing an inorganic doped composite gel electrolyte according to claim 1, characterized in that, The ratio of acrylic monomer to crosslinking agent is (1-7) mL:(0.01-0.1) g.
7. The method for preparing an inorganic doped composite gel electrolyte according to claim 1, characterized in that, The alkaline electrolyte is a mixed solution of potassium hydroxide and zinc acetate.
8. The method for preparing an inorganic doped composite gel electrolyte according to claim 1, characterized in that, The swelling treatment time is 12-48 h.
9. An inorganic doped composite gel electrolyte, characterized in that, It is prepared by the method described in claims 1 to 8.
10. The application of the inorganic doped composite gel electrolyte of claim 9 in a flexible zinc-air battery.